PENGEMBANGAN HUMAN CAPITAL DALAM KONTEKS MODAL SOSIAL - Widodo Widodo (Jurnal Keuangan dan Perbankan, 2011)
Rural Banks/BPR have a vitality and sustainability of business if they are able to create a unique advantagethat is superior in terms of customer information and business environment surrounding besides functioningas an intermediary institution. But in Semarang credit quality is still in the high risk level that is above themaximum limit of 5%. The condition is caused by the integration of human capital and social capital that isnot optimal. Therefore, this article aims to examine the model of human capital development so that it canimprove the performance of organization within the context of social capital. Retrieval method uses purposivesampling with 120 total samples. Later analysis technique uses Structural Equation Modelling (SEM) throughthe group management data which is processed based on high and low social capital. The study shows that thecontext of high social capital moderates the structure of the equation that affects human capital on organizationalperformance